Managing Core Competence of the Organization - Srivastava, Shirish C (Vikalpa, 2005)
Past studies on ‘core competence’ have deliberated either on the theoretical concept of core competence or its usefulness as a strategic tool for firms. In spite of a large number of papers on the subject, to the author's knowledge, there has been no study which spells out an actionable framework for leveraging the concept of core competence in creating competitive advantage for organizations. This perceptible gap in strategy literature is the prime motivation for this study. In this paper, the author views core competence as a ‘dynamic learned resource’ which is subject to continuous metamorphosis with changes in internal and external environment. The proposed ‘critical competence’ framework integrates the various studies on core competence and puts forth an all-encompassing practicable methodology to be utilized by firms for sustained success. Critical competence is the ability of a firm to successfully identify, nurture, develop, upgrade, and deploy its hierarchy of competencies to attain sustainable competitive advantage. In the process of proposing and explaining the framework for critical competence, this paper makes four major contributions: First, it provides a consolidated and comprehensive literature review on the subject of core competence which can be used by academics for future studies on the subject. Second, the proposed framework for critical competence shows that the possession of meta/core competencies will in itself not result in competitive advantage; rather, it is important to understand how these competencies are utilized for adding value to the firm. Third, the proposed critical competence framework serves as a tool for analysing the past success/failure and also serves as a guide for charting out the future strategy of firms. Fourth, through the example of Indian Railways, the paper illustrates the ‘descriptive capability’ of the proposed critical competence framework. The proposed framework helps us conclude that competencies in an organization need to be continuously nurtured, developed, and also abandoned. Critical competence emerges as a universal competence which is at the highest level in the hierarchy of competencies and is a prerequisite for attaining sustainable competitive advantage.